Nikel Laterit Pulau Gag: Menelusuri Proses Terbentuknya dan Implikasinya dalam Industri Pertambangan - Jarot, Jarot Pujiono; Retno Astuti, Theophila Listiyani (Retii, 2023)
The nickel laterite on Gag Island has had a significant impact on the mining industry, with major economic benefits and noteworthy social and environmental impacts. This research aims to understand the formation, characteristics, impacts, and management of nickel laterite on Gag Island through literature studies, field surveys, and laboratory analysis. Gag Island has ophiolite rocks that contain nickel, and limonite nickel is used in the HPAL battery industry. In contrast, saprolite nickel is used in the production of Ferro-Nickel (FeNi) with RKEF technology. The Gag Island laterite nickel mine has environmental impacts related to waste processing and water use in nickel extraction, requiring large investments in infrastructure, processing technology, regulatory compliance, and human resources. Further research is needed to understand the characteristics of Gag Island nickel laterite and address the challenges of facing increasing global nickel demand.